Long-term clinical outcome after thiopurine discontinuation in elderly IBD patients. (2nd November 2021) - Jorissen, C.; Verstockt, B.; Schils, N.; Sabino, J.; Ferrante, M.; Vermeire, S.
Abstract: Introduction and aim: Thiopurines – although used frequently in inflammatory bowel diseases (IBD) – carry a significant safety risk, particularly with prolonged use and/or in elderly patients. Stopping therapy, however, may trigger relapses. We assessed the long-term outcome of elderly IBD patients after discontinuation of thiopurine while in clinical remission. Methods: Electronic medical records from IBD patients >60 years whoever received thiopurine treatment were reviewed. Patients who stopped thiopurine after 60 years of age while in clinical and/or endoscopic remission were included. Long-term outcomes included duration of clinical remission, time to clinical relapse, and development of malignancy. Results: In total, 142 patients receiving thiopurines while they were >60 years were identified. Ninety-one patients stopped thiopurines at >60years while in clinical and/or endoscopic remission. After a median follow-up of 66 months, 28 (30.8%) developed a clinical relapse. The median duration of TP therapy in relapses was significantly shorter than in patients who remained in remission (median 45 vs. 103 months, respectively; p  = .005). After relapse, 10 patients started a biological (36%) and seven received steroids (25%). Surgery was needed in 36% of patients (10/28). Overall, 26 malignancies developed. Conclusion: Discontinuation of TP in elderly IBD patients in clinical and/or endoscopic remission results in sustained clinical remission in two-thirds of patients. Patients who flare can mostly be rescued with biologicals although one-third necessitate surgery. A significant proportion of patients developed malignancies under but also after thiopurines discontinuation, indicating that these patients necessitate a continued close follow-up. Decision-making in this vulnerable subgroup of patients remains difficult.